Modeling of an Overactuated Vehicle in Simscape Multibody for the Characterization of Suspension and Steering Actuation Systems. - Alcázar-Vargas, Manuel Gonzalo; Pérez-Fernández, Javier; Castillo-Aguilar, Juan Jesús; Cabrera-Carrillo, Juan Antonio (My University, 2023)
Overactuated systems are increasingly among us. They are used for applications in vehicles, aeronautics and robotics, among others [1, 2]. These systems have a number of advantages, among which we can mention that there are multiple (or infinite) solutions for a given problem. More specifically, in the case of overactuated vehicles, similar states of the system can be achieved in many different ways. These systems are still under development, especially in the field of vehicle dynamics. For example, there are various steer-by-wire algorithms, when the steering of the vehicles is independent, or brake blending strategies. In this work, a part of an overactuated vehicle is designed and validated. This multiphysics model allows to know the plant of the system in much more depth in order to develop control algorithms. More specifically, by modeling the delay of the systems and the nonlinear relationships inherent to multibody systems, much more accurate predictive control can be performed. These results allow a previous validation of the control algorithms in the test platform vehicle being manufactured and developed by the research group, greatly accelerating the control process of each of the overactuated systems of the vehicle.
Keywords: Vehículos - Sistemas de control; Vehicle dynamics; Simscape; Multibody dynamics